Refining Strategy: A Second Bid at Critical Interpretive Synthesis for Collection Building - Bales, Stephen; Sare, Laura (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
This paper reports on an on-going project to adapt critical interpretive synthesis (CIS), an interpretive method for synthesizing collections of both quantitative and qualitative research reports, for practical use by librarian subject selectors in current awareness activities and collection development. The authors critically assess a previous attempt at CIS for collection development—one that involved the subject area of journalism and popular culture—to inform and update their analytical strategies and streamline the method. These strategies are implemented in a second bid at CIS involving current research in philosophical ethics. It is determined that strategic shifts in both sampling and qualitative analytical procedures do much towards improving CIS’s potential as a practical tool.